1999
DOI: 10.1074/jbc.274.14.9427
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-induced S-Glutathionylation and Inactivation of Glyceraldehyde-3-phosphate Dehydrogenase

Abstract: S-Nitrosylation of protein thiol groups by nitric oxide (NO) is a widely recognized protein modification. In this study we show that nitrosonium tetrafluoroborate (BF 4 NO), a NO؉ donor, modified the thiol groups of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) by Snitrosylation and caused enzyme inhibition. The resultant protein-S-nitrosothiol was found to be unstable and to decompose spontaneously, thereby restoring enzyme activity. In contrast, the NO-releasing compound S-nitrosoglutathione (GSNO) promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
196
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(205 citation statements)
references
References 27 publications
9
196
0
Order By: Relevance
“…Reversible oxidation of the active site of protein tyrosine phosphatase-1B has been associated with control of biological function in redox signaling (39). Oxidation of Cys by S-glutathionylation (GS-ylation) regulates glyceraldehyde 3-phosphate dehydrogenase (125) and caspase-3 (173). Cys residues are present in active sites of detoxification enzymes such as glutathione transferases, cytochromes P-450, Trxs, and peroxiredoxins.…”
Section: The Redox Hypothesismentioning
confidence: 99%
“…Reversible oxidation of the active site of protein tyrosine phosphatase-1B has been associated with control of biological function in redox signaling (39). Oxidation of Cys by S-glutathionylation (GS-ylation) regulates glyceraldehyde 3-phosphate dehydrogenase (125) and caspase-3 (173). Cys residues are present in active sites of detoxification enzymes such as glutathione transferases, cytochromes P-450, Trxs, and peroxiredoxins.…”
Section: The Redox Hypothesismentioning
confidence: 99%
“…The impact of the residues surrounding a thiol was studied using GAPDH as a model. GAPDH Cys-149 was shown to be activated by an adjacent histidine, which deprotonates it to render it a stronger nucleophile, enabling cleavage of the S-N bond within GSNO resulting in either S-glutathiolation or S-nitrosation [19]. Pérez-Mato et al described the crystal structure of methionine adenosyl transferase and found Arg-357 and Asp-363 are in proximity to the active site Cys-131.…”
Section: A Consensus Motif For Selective and Targeted Protein S-nitromentioning
confidence: 99%
“…More recently GAPDH has also been described as a cardiac trans-nitrosylase in the heart, transferring NO between proteins [33]. However GAPDH is also regulated by disulfide formation at the very same Cys-150 site, for example undergoing both S-glutathiolation and S-nitrosation in response to GSNO [19]. Each of these modifications inhibited the dehydrogenase activity of GAPDH in vitro, but when only S-nitrosation was induced activity returned within 30 minutes -whereas inhibition by S-glutathiolation did not [108].…”
Section: Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the case of enzymes such as glyceraldehyde phosphate dehydrogenase, cAMPdependent protein kinase, creatine kinase, and protein kinase C, the altered enzyme activities by S-glutathionylation could be detected using biochemical assays (16,35,53,60,79,96,130). For ion channels, patch-clamp electrophysiology is the gold standard to test ion channel function and Ca + + imaging is also commonly used to study a variety of Ca + + -permeable channels.…”
Section: Functional Assaysmentioning
confidence: 99%